2008
DOI: 10.1002/rcs.178
|View full text |Cite
|
Sign up to set email alerts
|

New visualization tools: computer vision and ultrasound for MIS navigation

Abstract: Echo Point provided significantly improved results (p < 0.001) over conventional digitization where mean tilt errors exceeded 20 degrees . The Echo Morphing experiments demonstrated that with a reasonable number of points (ca. 1000) and initial attitude (IA) error (ca. 5-10 mm and 5-10 degrees ) we can obtain an average accuracy of approximately 1 mm that is sufficient for most of clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…This technology is an adaptation of the Bone Morphing using ultrasound. To verify our hypothesis concerning the error related to the percutaneous palpation and second to validate the Echo-Point ® technology, we performed a cadaver study comparing different acquisition conditions [15,16]. The results of this study confirmed that the cutaneous APP is not reliable to estimate the bony APP with major discrepancies between the two planes, more than 20 for the obese patients in the sagittal plane.…”
Section: Technological Limitssupporting
confidence: 69%
See 1 more Smart Citation
“…This technology is an adaptation of the Bone Morphing using ultrasound. To verify our hypothesis concerning the error related to the percutaneous palpation and second to validate the Echo-Point ® technology, we performed a cadaver study comparing different acquisition conditions [15,16]. The results of this study confirmed that the cutaneous APP is not reliable to estimate the bony APP with major discrepancies between the two planes, more than 20 for the obese patients in the sagittal plane.…”
Section: Technological Limitssupporting
confidence: 69%
“…Our results also confirmed the potential interest of the Echo-Point ® technology for the acquisition of the APP. The next step will be the clinical validation of these technologies [15,16]. …”
Section: Technological Limitsmentioning
confidence: 99%
“…4,13 Intraoperatively, the preregistered data are matched to the patient's individual coordinates by identifi cation and palpation of various landmarks. 14 The major disadvantage of these systems is the associated exposure to ionizing radiation. 13 This article presents the preliminary results of 10 patients operated with a novel 3-D freehand ultrasound system for navigated THA, highlighting its clinical applicability, specifi c problems, and limitations.…”
Section: E816mentioning
confidence: 99%
“…From a number of these partial images the shape and volume of the complete object could be reconstructed using interpolation or morphing techniques [10]. The possibility is strongly suggested by the images in Fig.…”
Section: Medical Imager Capabilitymentioning
confidence: 99%